Design and Development of Supporting Applications “E-MPKK” For Leraning Media of Midwife and Enterpreneurship Managament Clinic Practice - Yuseva Sariati; Ningrum Paramita Sari; Harun Al Rasyid; Suryo Ediyono (Indonesian Journal of Global Health Research, 2022)
Learning Center for Midwifery Service Management and Entrepreneurship to manage management reports, proposals, and role plays. The first purpose and benefit of this research is to design and build a prototype software application "E-MPKK" as a Learning Media for Clinical Practice Management of Midwifery and Entrepreneurship Services for Midwifery Department Students, FKUB so that the learning process is more effective and efficient, including easy access to reporting, monitoring student assignments, and the effectiveness of the duration of clinical guidance between lecturers and students. With this software application, students are expected to be able to analyze the correct information with the right method and time. The right time is meant to shorten the time to work on data collection, problem analysis, and making strategic plans. the process of storing the resulting soft file. assessment, analysis results, and planning to be better, structured, and measurable. With this software application students can analyze the correct information with the right method and time. storage of soft files of assessment results, analysis results, and planning to be better, structured, and measurable. by assessing the effectiveness and efficiency of working on reports with software applications. With this software application, it is expected that Midwifery Service Management reporting will be more effective; and reporting time is shorter, storage is also better and safer and reduces paper usage With this software application students can analyze the correct information with the right method and time. storage of soft files of assessment results, analysis results, and planning to be better, structured, and measurable. by assessing the effectiveness and efficiency of working on reports with software applications. With this software application, it is expected that Midwifery Service Management reporting will be more effective; and reporting time is shorter, storage is also better and safer and reduces paper usage With this software application students can analyze the correct information with the right method and time. storage of soft files of assessment results, analysis results, and planning to be better, structured, and measurable. by assessing the effectiveness and efficiency of working on reports with software applications. With this software application, it is expected that Midwifery Service Management reporting will be more effective; and reporting time is shorter, storage is also better and safer and reduces paper usage With this software application, it is expected that Midwifery Service Management reporting will be more effective; and reporting time is shorter, storage is also better and safer and reduces paper usage With this software application, it is expected that Midwifery Service Management reporting will be more effective; and reporting time is shorter, storage is also better and safer and reduces paper usage.